Construction of a catalytically active iron superoxide dismutase by rational protein design - Pinto, Ann L. (The National Academy of Sciences of the USA, 1997)
The rational protein design algorithm DEZYMER was used to introduce the active site of nonheme iron superoxide dismutase (SOD) into the hydrophobic interior of the host protein, Escherichia coli thioredoxin (Trx), a protein that does not naturally contain a transition metal-binding site. Reconstitution of the designed protein, Trx-SOD, showed the incorporation of one high-affinity metal-binding site. The electronic spectra of the holoprotein and its N(3)(−) and F(−) adducts are analogous to those previously reported for native {Fe(3+)}SOD. Activity assays showed that {Fe(3+)}Trx-SOD is capable of catalyzing the dismutation of the superoxide anion; comparative studies with the unrelated wild-type E. coli iron SOD indicated that {Fe(3+)}Trx-SOD catalyzes the dismutation reaction at a rate on the order of 10(5) M(−1)s (−1). The ability to design catalytically competent metalloenzymes allows for the systematic investigation of fundamental mechanistic questions concerning catalysis at transition metal centers.